Catcher in the rel: Nanoparticles-antibody conjugate as NF-κB nuclear translocation blocker. (July 2020) - Chen, Yi-Ping; Chen, Chien-Tsu; Liu, Tsang-Pai; Chien, Fan-Ching; Wu, Si-Han; Chen, Peilin; Mou, Chung-Yuan
Abstract: Transcription factor complex NF-κB (p65/p50) is localized to the cytoplasm by its inhibitor IκBα. Upon activation, the Rel proteins p65/p50 are released from IκBα and transported through nuclear pore to affect many gene expressions. While inhibitions of up or down stream signal pathways are often ineffective due to crosstalks and compensations, direct blocking of the Rel proteins p65/p50 has long been proposed as a potential target for cancer therapy. In this work, a nanoparticle/antibody complex targeting NF-κB is employed to catch the Rel protein p65 in perinuclear region and thus blocking the translocation near the nuclear pore gate. TAT peptide conjugated on mesoporous silica nanoparticles (MSN) help non-endocytosis cell-membrane transducing and converge toward perinuclear region, where the p65 specific antibody performed the targeting and catching against active NF-κB p65 effectively. The size of the p65 bound nanoparticle becomes too big to enter nucleus. Simultaneous treatment of mice with the hybrid MSN and doxorubicin conferred a significant therapeutic effect against 4T1 tumor-bearing mice. The new approach of anti-body therapy targeting on transcription factor with "nucleus focusing" and "size exclusion blocking" effects of the antibody-conjugated nanoparticle is general and may be applicable to modulating other transcription factors. Graphical abstract: Anti-p65 antibody-TAT conjugated mesoporous silica nanoparticles, designed as translocation blockers, are successful in cytoplasmic delivery, attacking NF-κB p65 and blocking p65 nuclear translocation through step 1–3. Such unique hybrid nanoparticles highlight intriguing "nucleus focusing" and "size exclusion blocking" properties. Combining the strategy with chemotherapy drug Doxorubicin, promising therapeutic effect is in addition shown in 4T1 triple-negative breast cancer mouse model. Image 7